(untitled) (Conferencea, 2022)
Natural compounds are an inexhaustible source of drugs with various therapeutic effects. The study of the molecular mechanisms of the pathogenesis of a huge number of plant, animal and human diseases has shown that all of them are to some extent associated with the activation or suppression of free radical processes. Therefore, the search and study of regulators of such processes based on natural and synthetic raw materials remains relevant. All plant compounds in relation to animal organisms, to one degree or another, have an extremely wide spectrum of biological activity, due to the diversity of their chemical structure, and are currently in the center of scientific attention. In connection with the above, the search for antioxidants and the study of their inhibitory effect on the processes of free radical oxidation, uncontrolled lipid peroxidation, seems to be quite timely and in demand. Previously, polyphenolic compounds were isolated from the leaves of Plantago major L. and Rhus glabra, which we conventionally named Plantagin and Glabtan, respectively. Plantagin consists mainly of flavonoids and their glycosides. Glаbtan consists of hydrolysable tannins